2017
DOI: 10.20307/nps.2017.23.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Compounds from the Leaves ofKalanchoe proliferaand Their Cytotoxic Activity against P-388 Murine Leukimia Cells

Abstract: − Seven flavonoid compounds, kaempferol (1), quercetin (2), quercetin (6) and quercetin-3-O-rutinoside (7), were isolated from the methanolic extract of leaves of Kalanchoe prolifera. Compounds 1-7 were isolated for first time from this plant. These compounds were evaluated their cytotoxic activity against P-388 murine leukimia cells in vitro. Among those compounds kaempferol (1) and quercetin (2) showed strongest cytotoxic activity with IC 50 values of 4.45 ± 0.05 and 6.28 ± 0.02 μg/mL, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 26 publications
2
21
0
2
Order By: Relevance
“…The molecular weight (MW) of 1 was determined to be 302 amu based on the molecular ion peak ( ; one conjugated ketone carbon signal at δ C 177.12 (C-4) suggested that 1 was a flavonol. 1 was identified to be quercetin through intensive analysis of 2D-NMR (i.e., gHSQC and gHMBC) data as well comparison of the spectroscopic data with reported literature [16].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight (MW) of 1 was determined to be 302 amu based on the molecular ion peak ( ; one conjugated ketone carbon signal at δ C 177.12 (C-4) suggested that 1 was a flavonol. 1 was identified to be quercetin through intensive analysis of 2D-NMR (i.e., gHSQC and gHMBC) data as well comparison of the spectroscopic data with reported literature [16].…”
Section: Resultsmentioning
confidence: 99%
“…for C 30 H 39 O 7 m/z 511.2696) and nuclear magnetic resonance (NMR) data (Table 1), indicating the presence of twelve degrees of unsaturation. The ultraviolet (UV) spectrum showed maximum absorption at 284 nm, indicating the presence of an α, β-unsaturated ketone [13,14]. Infrared (IR) absorptions spectra suggested the presence of hydroxyl (3509 cm −1 ), aliphatic (2929 cm −1 ), carbonyl ester (1744 cm −1 ), α, β-unsaturated carbonyl (1670 cm −1 ), olefinic (1502 cm −1 ), gem-dimethyl (1366 and 1386 cm −1 ) and ether groups (1248 cm -14).…”
Section: Resultsmentioning
confidence: 99%
“…The NMR profiling of these fractions suggested the presence of flavonoids and iridoids. In fact, the known flavonoids, rutin ( 8 ) [ 28 ], kaempferol-7- O -rhamnosyl-3- O -glucopyranoside ( 9 ) [ 29 ], kaempferol-3- O -rutinoside ( 10 ) [ 30 ], and kaempferol-3- O -glucopyranoside ( 11 ) [ 28 ] were identified as constituents of fraction G ( Figure 3 ), along with two acylated iridoid glycosides ( 12 – 13 , Figure 5 ), one of them ( 13 ) isolated and characterized for the first time.…”
Section: Resultsmentioning
confidence: 99%